2022
DOI: 10.1186/s12889-022-12526-0
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis, soil transmitted helminthiasis, and malaria co-infections among women of reproductive age in rural communities of Kwale County, coastal Kenya

Abstract: Background Schistosoma haematobium, soil transmitted helminthes (STH), and malaria lead to a double burden in pregnancy that eventually leads to poor immunity, increased susceptibility to other infections, and poor pregnancy outcomes. Many studies have been carried out on pre-school and school aged children but very little has been done among the at risk adult population including women of reproductive age (WRA). Our current study sought to establish the risk factors and burden of co-infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 62 publications
4
15
0
Order By: Relevance
“…In our current study, the overall prevalence of Soil-Transmitted Helminthes infections among pregnant women was found to be 6.06% (95% CI: 4.11-8.86). This is in line with a community-based study done in Kwale County among pregnant women documented an overall prevalence of STH infections of 5.6% [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our current study, the overall prevalence of Soil-Transmitted Helminthes infections among pregnant women was found to be 6.06% (95% CI: 4.11-8.86). This is in line with a community-based study done in Kwale County among pregnant women documented an overall prevalence of STH infections of 5.6% [17].…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of hookworm was 4.8%, while that of T. trichiura was 1.2%, which is consistent with ndings from a similar study reporting hookworm and T. trichiura prevalence rates of 5.3% and 0.6%, respectively [17]. The prevalence of Soil-Transmitted Helminthes in our study is lower than that reported by Kihara et al, who documented a 24.8% prevalence of hookworm in women of reproductive age [18].The decline in the prevalence of Soil-Transmitted Helminthes could be attributed to the TUMIKIA project, conducted in Kwale between 2015 and 2017 [24], which involved the annual and bi-annual distribution of albendazole through both school-based and community-based Mass Drug Administration (MDA) programs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Malaria and schistosomiasis are widespread parasitic infections in tropical and subtropical regions including Ghana [ 4 , 5 ] and pose a double disease burden during pregnancy in coendemic areas. Disease burden seems to be greater in women of reproductive age [ 6 ], often leading to lowered immunity, increased susceptibility to other infections, and poor pregnancy outcomes [ 7 , 8 ]. Another critical complication of malaria and schistosomiasis is anaemia, which could have severe consequences on the health of the mother [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis, another known cause of anaemia [ 18 ], affects nearly 200 million people worldwide with considerable economic impact and morbidity [ 6 , 7 , 19 ]. As a disease of poverty, 97% of schistosomiasis infections and 85% of at-risk population live in Africa [ 20 ].…”
Section: Introductionmentioning
confidence: 99%